Exploring the neural correlates of the reversed letter effect: Evidence from left and right parietal patients. (23rd April 2019) - Mangano, Giuseppa Renata; Cipolotti, Lisa; Turriziani, Patrizia; Giammusso, Isabella; Smirni, Daniela; Zhaoping, Li; Bracco, Martina; Oliveri, Massimiliano
Highlights: We explored the neural correlates of the reversed letter effect in visual search. Two experiments on parietal patients and healthy controls were conducted. Right but not left parietal patients had this reversed letter effect. This finding supports the evidence for hemispheric specialization of attention. Abstract: To investigate the hemispheric lateralization of attentional processes during visual search tasks depending on the stimulus material embedding the target, twelve patients with unilateral left (n = 7) or right (n = 5) parietal lesions and 20 age and education matched healthy controls (HC) were recruited. We used a visual search task for a uniquely tilted oblique bar embedded in an object shape 'N' or in its mirror reversal 'И'. The accuracy and the averaged reaction times (RTs) in each stimulus type ('N' or 'И') were analysed. HC presented significantly longer RTs when the target bar was embedded in 'N' among its mirror reversed 'И' (p < .05). This "reversed letter effect" was also found in the right parietal patients (p < .001), while no evidence of a reversed letter effect was found in the left parietal patients.